2019
DOI: 10.1042/bsr20180268
|View full text |Cite
|
Sign up to set email alerts
|

The SLC34A2-ROS-HIF-1-induced up-regulation of EZH2 expression promotes proliferation and chemo-resistance to apoptosis in colorectal cancer

Abstract: Growing evidence has uncovered that plays an evident role in the progression in several types of tumors. However, the biological function and underlying molecular mechanisms of remain largely unknown. Here, we indicated that SLC34A2 expression was markedly increased in SW480 and HT29 cell line cells compared with that in normal colorectal epithelial cell line cells. Array analysis displayed that the expression of EZH2 (enhancer of zeste 2) decreased considerably when was knocked-down. We demonstrated that SLC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Two down‐regulated miRNAs named miR‐660‐3p and hsa‐miR‐4510 show the most interactions with DEGs. Both of them in our study could target some studied oncogenes in other studies including ADAM28, 25 HMGA1 26 and SLC34A2 27 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Two down‐regulated miRNAs named miR‐660‐3p and hsa‐miR‐4510 show the most interactions with DEGs. Both of them in our study could target some studied oncogenes in other studies including ADAM28, 25 HMGA1 26 and SLC34A2 27 …”
Section: Discussionmentioning
confidence: 84%
“…Both of them in our study could target some studied oncogenes in other studies including ADAM28, 25 HMGA1 26 and SLC34A2. 27 According to Shyian et al report, the relationship between expression of SLC34A2 and differentiation level of OV tumor cells was confirmed. So, it can be used as a possible marker in determination of cell differentiation.…”
Section: Discussionmentioning
confidence: 93%
“…It had been found that the expression level of LATS1 had decreased in serous ovarian cancer patients but this gene highly expressed in normal ovarian tissue [52,53]. SLC34A2 was proved to have an evident effect in the progression of several types of cancers, such as in ovarian cancer [54,55], breast cancer and non-small cell lung cancer [56,57]. The gene fusion of SLC34A2 and ROS1 played an important role in the progression of nonsmall cell lung cancer [58].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, increased ROS stabilize the HIF-1α protein inducing EZH2 overexpression. The silencing of SLC34A2 completely prevented EZH2 overexpression, as well as colorectal cell proliferation and chemo-resistance ( 80 ). Another mechanism through which HIF-1α can increase EZH2 expression has been demonstrated in prostate cancer cells.…”
Section: Hif–ezh2 Connectionmentioning
confidence: 99%